Design and Synthesis of (99m)TcN-Labeled Dextran-Mannose Derivatives for Sentinel Lymph Node Detection - Boschi, Alessandra (Pharmaceuticals (Basel), 2018)
Background: New approaches based on the receptor-targeted molecular interaction have been recently developed with the aim to investigate specific probes for sentinel lymph nodes. In particular, the mannose receptors expressed by lymph node macrophages became an attractive target and different multifunctional mannose derivate ligands for the labeling with (99m)Tc have been developed. In this study, we report the synthesis of a specific class of dextran-based, macromolecular, multifunctional ligands specially designed for labeling with the highly stable [(99m)Tc≡N](2+) core. Methods: The ligands have been obtained by appending to a macromolecular dextran scaffold pendant arms bearing a chelating moiety for the metallic group and a mannosyl residue for allowing the interaction of the resulting macromolecular (99m)Tc conjugate with specific receptors on the external membrane of macrophages. Two different chelating systems have been selected, S-methyl dithiocarbazate [H(2)N‒NH‒C(=S)SCH(3)=HDTCZ] and a sequence of two cysteine residues, that in combination with a monophosphine coligand, are able to bind the [(99m)Tc≡N](2+) core. Conclusions: High-specific-activity labeling has been obtained by simple mixing and heating of the [(99m)Tc≡N](2+) group with the new mannose-dextran derivatives.